Characterization of Full Length Sequence of JJ3 Isolated from Shade Tolerant Soybean - Nurul Khumaida; , Kisman; Didy Sopandie (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
The aim of this study was to characterize full length sequence of JJ3 isolated from shade tolerant soybean. The characterization of full length sequence involved analyses of structure of full length sequence, open reading frame (ORF) or coding sequence (CDS), and homology. The analyses of JJ3 full length sequence structure were done using GeneScanW program, coding sequence (CDS) or open reading frame (ORF) using ORF Finder program, and the homology of JJ3 full length sequence were done using BLAST and clustalW programs. Results showed that the full length sequence of JJ3 consisted of single exon and polyA. Single exon was a coding sequence (CDS) 633 bp produced open reading frame (ORF) with 210 amino acid deduction comprised of 136 conserved amino acids and 77 varied amino acids. The conserved domain of JJ3 produced functional protein, PsaD photosystem I (PSI) subunit, related to photosynthetic transport electron in PSI reaction center. The full length of JJ3 homolog to psaD, a gene encoding protein subunit photosystem I (PSI) related to mechanism of plant adaptation to shade stress, in wood tobacco (Nicotiana sylvestris), rice (Oryza sativa), tomato (Lycopersicon esculentum), barley (Hordeum vulgare), spinach (Spinacia oleracea), Arabidopsis (Arabidopsis thaliana), and potato (Solanum tuberosum).Key words: full length sequence, gene, homology, shade tolerant, soybean